2014
DOI: 10.1152/jn.00066.2014
|View full text |Cite
|
Sign up to set email alerts
|

Development of dendritic tonic GABAergic inhibition regulates excitability and plasticity in CA1 pyramidal neurons

Abstract: Synaptic plasticity rules change during development: while hippocampal synapses can be potentiated by a single action potential pairing protocol in young neurons, mature neurons require burst firing to induce synaptic potentiation. An essential component for spike timing-dependent plasticity is the backpropagating action potential (BAP). BAP along the dendrites can be modulated by morphology and ion channel composition, both of which change during late postnatal development. However, it is unclear whether thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 80 publications
7
33
0
Order By: Relevance
“…Previous studies have clearly demonstrated a role for tonic GABAergic conductances in the steady suppression of neuronal output, mediated by both membrane hyperpolarization and shunting of synaptic inputs (Farrant and Nusser, 2005;Lee and Maguire, 2014). Indeed, a5 subunit-containing GABAARs were recently shown to suppress the backpropagation of APs in PN dendrites and the opening of NMDA-type glutamate receptors (Groen et al, 2014;Schulz et al, 2018). Our present results are not inconsistent with this view.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have clearly demonstrated a role for tonic GABAergic conductances in the steady suppression of neuronal output, mediated by both membrane hyperpolarization and shunting of synaptic inputs (Farrant and Nusser, 2005;Lee and Maguire, 2014). Indeed, a5 subunit-containing GABAARs were recently shown to suppress the backpropagation of APs in PN dendrites and the opening of NMDA-type glutamate receptors (Groen et al, 2014;Schulz et al, 2018). Our present results are not inconsistent with this view.…”
Section: Discussionsupporting
confidence: 78%
“…5g. Here, the presence of rectifying tonic inhibition attenuates electrotonic spread of AP's down the dendritic tree, as previously experimentally demonstrated in pyramidal neurons (28). This enhances the somato-dendritic voltage gradient and, by Ohm's law, also increases somato-dendritic current flow.…”
Section: ) Tonic Inhibition Enhances Action Potential Repolarisationsupporting
confidence: 67%
“…2b). The presence of non-rectifying tonic inhibition also induced significant differences in ∆ gain between fast spiking and non-fast spiking models, however differences were lower compared to rectifying tonic inhibition and increased gain within non-fast spiking models not observed (-5.4% ± 1.0 vs -0.7% ± 0.4, Welch's t-test, , t (28) = -4.4, **P < 0.001). We observed similar findings for EGABA of -80mV ( Supplementary Fig.…”
Section: Fig 2: Impact Of Tonic Inhibition Upon Gain In Interneuron mentioning
confidence: 89%
See 1 more Smart Citation
“…By interfering with Ca 2+ -dependent processes by pharmacology and multi-synaptic stimulation (Meredith et al, 2003;Tsukada et al, 2005;Nishiyama et al, 2010;Groen et al, 2014), GABA A -receptor-mediated dendritic inhibition has been shown to modulate spike-timing-dependent plasticity rulessometimes even converting LTP-inducing into LTD-inducing stimuli. Addressing inhibition of Ca 2+ processes more directly, a number of elegant studies have described dendritic inhibition of Ca 2+ -dependent spikes upon activation of single (Larkum et al, 1999) or multiple (Miles et al, 1996;Tsubokawa and Ross, 1996) dendrite-targeting inhibitory interneurons in brain slices, as well as in vivo (Murayama et al, 2009).…”
Section: Introductionmentioning
confidence: 99%